20.5k views
2 votes
What is the answer to s/3-7/6+2s/5=3s/4 s= -----

User Krsteeve
by
5.8k points

1 Answer

4 votes

Answer:

s = -70 in the given expression.

Explanation:

Here, the given expression is:


(s)/(3) - (7)/(6) + (2s)/(5) = (3s)/(4)

Now, to find the value of s, we need to simplify the given expression:

We get:


(s)/(3) - (7)/(6) + (2s)/(5) = (3s)/(4)\\\implies (s)/(3)  + (2s)/(5) -  (3s)/(4)  = (7)/(6)\\\implies(20(s) + 12(2s) - 15(3s))/(60)    = (7)/(6)\\\implies (20 s  + 24 s - 45 s)/(60)   = (7)/(6)\\\implies (-s)/(60) = (7)/(6)\\\implies s = (7)/(6) * (-60)  = - 70\\\implies s  = (- 70)

Hence, s = -70 in the given above expression.

User Angelo Angeles
by
4.9k points